2D multichannel seismic reflection processed data (GI Gun entire dataset) of RV METEOR during cruise M94, Campeche Bank, Gulf of Mexico - Christian Hübscher (PANGAEA, 2023)
Seismic reflection data were collected during RV METEOR expedition M94 in 2013 (Hübscher et al., 2014) at the eastern Campeche Bank in the southern Gulf of Mexico. The source signal was generated by two GI-Guns with generator volumes of 45 in3 and injector volumes of 105 in3. Both BI-Guns were operated in true "GI-Mode". The 16-channel analog streamer had an active length of 100 m. Sample rate was 1 ms. The weather conditions were rather harsh, so noise level was high. The undamped passband of the frequency filter was between 20 and 200 Hz. Further processing steps included predictive deconvolution, spherical divergence correction, stacking, time-migration, white-noise suppression by the technique described by Butler (2012) as implemented in Schlumbergers VISTA® processing package, and fx-deconvolution. The purpose was to image mass failures at the eastern rim of the Campeche Bank as the consequence of the Chicxulub meteorite impact at the Cretaceous-Paleogene boundary, and the plastered contourite drift that developed at the collapsed carbonate platform. The data are uploaded as SEG-Y data. Shot, receiver and CMP coordinates are in UTM27 at standard binary positions.